2023
DOI: 10.1002/cyto.b.22115
|View full text |Cite
|
Sign up to set email alerts
|

Increased IFN‐γ+ and TNF‐α+ mucosal‐associated invariant T cells in patients with aplastic anemia

Abstract: Background Aplastic anemia (AA) is known as an autoimmune disease in which T cell activation is aberrant. It has been reported that unconventional T cells, mucosal‐associated invariant T (MAIT) cells, play an important role in several autoimmune diseases, but it is unclear if they are involved in AA. Methods In this study, we for the first time analyzed the proportions, phenotypes, and cytokine properties of MAIT cells in AA by flow cytometry. Results We found that the percentage of circulating MAIT cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Proteins circulating in the blood are critical for predicting human disease and are often used as biomarkers for clinical decision making (Folkersen et al, 2020). Previous studies have revealed the role of TNF superfamily members in cancer (Flieswasser et al, 2022;Curtis et al, 2023), autoimmune diseases (Tian et al, 2020;Chen et al, 2023), and respiratory diseases (Cho et al, 2020;Cross et al, 2023), which have been proven to be involved with severe COVID-19 (Zhang et al, 2021). Our genetic evidence suggests that FAS is positively associated with the severity of COVID-19 and that CD40 is protective against severe COVID-19.…”
Section: Discussionsupporting
confidence: 50%
“…Proteins circulating in the blood are critical for predicting human disease and are often used as biomarkers for clinical decision making (Folkersen et al, 2020). Previous studies have revealed the role of TNF superfamily members in cancer (Flieswasser et al, 2022;Curtis et al, 2023), autoimmune diseases (Tian et al, 2020;Chen et al, 2023), and respiratory diseases (Cho et al, 2020;Cross et al, 2023), which have been proven to be involved with severe COVID-19 (Zhang et al, 2021). Our genetic evidence suggests that FAS is positively associated with the severity of COVID-19 and that CD40 is protective against severe COVID-19.…”
Section: Discussionsupporting
confidence: 50%
“…The last article in this issue (Chen, Zhang, et al, 2023) studied mucosal‐associated invariant T cells (MAIT) (Godfrey et al, 2019) in aplastic anemia (AA), a type of bone marrow failure directly linked to abnormal immune responses. MAIT cells exhibit an effector‐memory phenotype and express several NK receptors such as NKG2D and CD161 and play an important role in the development of autoimmune diseases.…”
mentioning
confidence: 99%
“…The last article in this issue (Chen, Zhang, et al, 2023) studied mucosal-associated invariant T cells (MAIT) (Godfrey et al, 2019)…”
mentioning
confidence: 99%